Analysis on impedance characteristics and research on pantograph rising and dropping overvoltage of CFRP carbody - XU Yue; FENG Yuming; BAI Gang; BIAN Yongliang; WANG Fuqiang; GUO Wenqing (机车电传动)
In order to evaluate the over-voltage damage of CFRP (Carbon fiber reinforced polymer/plastic) car body due to its poorer conductivity than traditional aluminum alloy car body, the impedance characteristics of CFRP were analyzed and tested, and the surge overvoltage circuit model of CFRP train body was established based on the improved design of semi-CFRP semi-aluminum alloy structure. The transmission characteristics of surge overvoltage of the cab body at the moment of pantograph raising/dropping were analyzed by simulation. The results show that the maximum overvoltage in pantograph raising reaches 2.4 kilovolts, which is a potential safety hazard for on-board equipment. It is proposed that the metal grounding network is installed in cab body to provide grounding points for on-board equipment, which is effectively ensures the safety of the on-board equipment.